Oral fat loading test: a reliable procedure for the study of fat malabsorption in children. - Jonas, A (1979)
Oral triglyceride (TG) loading tests were performed in four groups of children: normal controls, patients with chronic nonspecific diarrhoea (CND), biopsy-proved mucosal pathology (MP), and disturbed intraluminal fat malabsorption (IFM). The rise of plasma TG levels greater than or equal to 55 mg/100 ml (greater than or equal to 0.6 mmol/l) can discriminate between patients with gastrointestinal disease and normal controls or patients with functional disturbances. The postmeal plasma TG rise correlates well with the coefficient of fat absorption (CFA) in normal subjects, patients with CND, and patients with IFM, but not in patients with MP who showed a disproportionally low plasma TG rise compared with their CFA. This test can serve as a useful tool in diagnosis and clinical evaluation for children with gastrointestinal disorders.